A New Approach to the Synthesis of Catena-compounds - Larkem, H.; Larkem , A. (Asian Journal of Chemistry, 2016)
This paper describes the preparation of the macrocyclic cyclo-pentadienone (2), which was accomplished by the following method from diacetylenic ketone. Benzil was condensed with a long chain ketone to give (1) and the macrocycle (2) formed in a subsequent step.